Oral Administration of Compound Probiotics Improved Canine Feed Intake, Weight Gain, Immunity and Intestinal Microbiota - Xu, Haiyan; Huang, Weiqiang; Hou, Qiangchuan; Kwok, Lai-Yu; Laga, Wuri; Wang, Yanjie; Ma, Huimin; Sun, Zhihong; Zhang, Heping (Frontiers in Immunology, 2019)
Probiotics have been used successfully to promote human and animal health, but only limited studies have focused on using probiotics to improve the health of hosts of different age. Canine microbiome studies may be predictive of results in humans because of the high structural and functional similarity between dog and human microbiomes. A total of 90 dogs were divided into three groups based on dog age (elderly group, n=30; young group, n=24; and training group, n=36). Each group was subdivided into two subgroups, with and without receiving daily probiotic feed additive. The probiotic feed additive contained three different bacterial strains, namely Lactobacillus casei Zhang, Lactobacillus plantarum P-8, and Bifdobacterium animalis subsp. lactis V9. Serum and fecal samples were collected and analyzed at four different time points, i.e. days 0, 30, and 60 of probiotic treatment, and 15 days after ceasing probiotic treatment. The results demonstrated that probiotics significantly promoted the average daily feed intake of the elderly dogs (P<0.01) and the average daily weight gain of all dogs (P<0.05), enhanced the level of serum IgG (P<0.001), IFN-α (P<0.05), and fecal SIgA (P<0.001), while reduced the TNF-α (P<0.05). Additionally, probiotics could change the gut microbial structure of elderly dogs and significantly increased beneficial bacteria (including some Lactobacillus species and Faecalibacterium prausnitzii) and decreased potentially harmful bacteria (including Escherichia coli and Sutterella stercoricanisin), and the elderly dogs showed the strongest response to the probiotics; the relative abundance of some of these species correlated with certain immune factors and physiological parameters, suggesting that the probiotic treatment improved the host health and enhanced the host immunity by stimulating antibody and cytokine secretion through regulating canine gut microbiota. Furthermore, the gut microbiota of the elderly dogs shifted towards a younger-like composition at day 60 of probiotic treatment. Our findings suggested that the probiotic treatment effects on canine health and immunity were age-related and have provided interesting insights into future development of probiotic-based strategies to improve animal and human health.